The Capital Structure Determinants on Banking Sector of Western Balkan Countries - Ahmeti, Yllka; Kalimashi, Albina; Ahmeti, Ardi; Ahmeti, Skender (Ekonomika, 2023)
The study examines the capital structure of the Western Balkan banking industry across the period 2015 - 2020. Forty-seven of the total Western Balkan-based commercial banks were included in the study. By constructing a balanced panel, this study uses pooled ordinary least squares fixed and random effects regressions to examine the relationship between bank book leverage as the dependent variable and bank-specific explanatory variables that include profitability, leverage ratio, bank size, earnings volatility, collateral, growth opportunities, and liquidity. These reports are examined using linear regression analysis. The study shows a significant positive relationship between profitability and book leverage for the period studied. In contrast, leverage ratio, earnings volatility, collateral, growth, and liquidity significantly negatively impact the book leverage of Western Balkan banks.The findings have practical implications for bank executives. They will assist them in identifying the bank-specific factors that influence the capital structure and selecting values that promote optimal capital structure. The findings of this study can help regulators develop an effective prudential framework. This study opens up new avenues for further research in this area for academics, researchers, and analysts.
Keywords: Capital structure; Book leverage; Robust Fixed effects; Banking sector; Western Balkan